Budget Deficits and Public Borrowing Instruments in an Islamic Economic System (American Journal of Islam and Society, 1994)
In this rapidly changing world, several countries and political movements,especially in the Middle East, are calling for the establishment ofan Islamic economic system. This paper seeks to explain the area of publicborrowing in such a system and to explore its use in today’s worldIn the literatwe, the term “budget deficit” denotes the gap betweenpublic revenue and expenditures. Revenues normally come from taxationand public property, while expenditures may cover development projectsand cumnt governmental expenses. In general, such a deficit is bridgedby increasing revenues, reducing expenditures, internal borrowing (i.e.,from the public commercial banks or the central bank), and by externalborrowing. In the past, governments used to borrow from their richcitizens only to meet the financial needs associated with wars and naturalcalamities. Today, however, public bornwing has become a major featureof contemporary economies in both developed and developing countries.This paper cosists of four sections: the principles of financing inIslam, the Islamic point of view on the provision of public goods, variousinstruments for public resource mobilization that can be developed on thebasis of Islamic principles of financing, and a conclusion.The Principles of FinancingThere are several recorded cases of public borrowing during the timeof the ptophet, as well as othets by the ‘AbWd and the Ottoman governments(Siddiqui 1992). This practice has petsisted into the modem era,as evidenced by Egypt and the Ottoman Empire during the middle of the ...